Tinjauan Hukum Penggunaan Surat Kuasa Khusus Guna Memberikan Perlindungan Hukum Bagi Pemilik Hak Atas Tanah - Mulyani, Tri; Siswanda, Yoga Dwi; Sulistyarini, Dyah Ayu (JURNAL PENELITIAN SERAMBI HUKUM, 2024)
This study aims to identify and analyze the legal protection for land owners who are victims of misuse of power of attorney to safeguard land, and the legal implications for parties involved in using the power of attorney. The research methods used include: the type of research is Normative Juridical, with analytical descriptive specifications. The data used is secondary data with qualitative data analysis. The research results show that legal protection for land owners who are victims of the use of a special power of attorney is regulated in Article 1794, Article 1795 and Article 1796 of the Civil Code. Based on Article 1797 of the Civil Code, the recipient of the power of attorney may not do anything that exceeds his or her power. The legal implications include a special power of attorney in legal actions including 3 parties, namely: First the person giving the power of attorney, Second, the recipient of the power of attorney, and the related third party, namely the Notary and PPAT who convey the code of ethics.